2012
DOI: 10.1371/journal.pone.0046577
|View full text |Cite
|
Sign up to set email alerts
|

The Mammalian DM Domain Transcription Factor Dmrta2 Is Required for Early Embryonic Development of the Cerebral Cortex

Abstract: Development of the mammalian telencephalon is precisely organized by a combination of extracellular signaling events derived from signaling centers and transcription factor networks. Using gene expression profiling of the developing mouse dorsal telencephalon, we found that the DM domain transcription factor Dmrta2 (doublesex and mab-3-related transcription factor a2) is involved in the development of the dorsal telencephalon. Consistent with its medial-high/lateral-low expression pattern in the dorsal telence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
83
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(91 citation statements)
references
References 40 publications
8
83
0
Order By: Relevance
“…1 B and D). During development, Dmrta2 expression is restricted to the dorsal telencephalon, where it is coexpressed with Pax6 but in an opposite gradient (12,13,24). Consistent with its expression in vivo, we found that Dmrta2 and Pax6 staining largely overlapped in ESC-derived NPCs localized in neural rosettes, from which Eomes + basal progenitor cells could be seen extending distally (Fig.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…1 B and D). During development, Dmrta2 expression is restricted to the dorsal telencephalon, where it is coexpressed with Pax6 but in an opposite gradient (12,13,24). Consistent with its expression in vivo, we found that Dmrta2 and Pax6 staining largely overlapped in ESC-derived NPCs localized in neural rosettes, from which Eomes + basal progenitor cells could be seen extending distally (Fig.…”
Section: Resultssupporting
confidence: 80%
“…Although Dmrt1 is not expressed by cortical NPCs, our data suggest significant overlaps in the regulatory targets of different Dmrt proteins. This is of particular interest because of the similar expression patterns of Dmrt3, Dmrta1, and Dmrta2 in the dorsal telencephalon, suggesting a potential for functional redundancy (13,24). A similar but less severe phenotype as that seen in Dmrta2 null mutants has been observed in mice with a Dmrt3 null mutation, further supporting the idea that the two factors have overlapping functions in cortical development (12)(13)(14).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations